Analisis Penyajian Laporan Keuangan Usaha Kecil Berbasis Technology Acceptance Model (TAM) dengan Ukuran Usaha sebagai Variabel Moderasi - Asrori Asrori; Frandi Charisma (Jurnal Riset Keuangan dan Akuntansi, 2020)
Financial statements are financial records of an entity or company in an accounting period. Financial statements are used to measure the performance of small businesses and as a basis for making business decisions. This study aims to examine the side of the internal influence of small businesses, namely perceptions of usability and perceptions of ease of use, and test the effect of business measures in moderating the effect of independent variables on dependent variables. This research is survey research. This study uses the Structural Equation Model (SEM) analysis method. Hypothesis testing uses the SmartPLS 3.0 program. The results of the study indicate that perceived usefulness has a significant positive effect on the presentation of financial statements, business measures reinforce the influence of perceived usefulness in the presentation of financial statements. While the perception of ease of use does not have a significant effect on the presentation of financial statements, and business size is not able to strengthen the influence of perceptions of ease of use on the presentation of financial statements. The suggestion for the next researcher is to add independent variables.Keywords: Perception of Use; Ease of Use; Presentation of Financial Statements